2004
DOI: 10.1002/bdra.20076
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a molecular mechanism of teratogenicity of SB‐236057, a 5‐HT1B receptor inverse agonist that alters axial formation

Abstract: We present experimental evidence that the mechanism of SB-236057 teratogenicity includes transcriptional alterations to the Notch1-En[spl] pathway. In addition, alterations in HNF3-beta expression were similar to those induced by cyclopamine. The relationships between r-esp1 with Notch1 and shh signaling pathways and potential mechanisms of SB-236057 teratogenicity are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Other compounds found in this cluster, such as haloperidol and reserpine, were not specifically associated with activation of the estrogen receptor pathway. Another compound, the teratogen cyclopamine, acts through the sonic hedgehog pathway to downregulate estrogen receptor-α protein, and DPharma34, also known as SB-236057, has teratogenic effects through pathways similar to those of cyclopamine 28 . Inspection of the compound profiles in cluster 48 and comparison with estrogen receptor agonists (cluster 28) revealed tissue factor (TF) in the 3C system as a discriminating activity of particular interest (Fig.…”
Section: Chemical Clusteringmentioning
confidence: 99%
“…Other compounds found in this cluster, such as haloperidol and reserpine, were not specifically associated with activation of the estrogen receptor pathway. Another compound, the teratogen cyclopamine, acts through the sonic hedgehog pathway to downregulate estrogen receptor-α protein, and DPharma34, also known as SB-236057, has teratogenic effects through pathways similar to those of cyclopamine 28 . Inspection of the compound profiles in cluster 48 and comparison with estrogen receptor agonists (cluster 28) revealed tissue factor (TF) in the 3C system as a discriminating activity of particular interest (Fig.…”
Section: Chemical Clusteringmentioning
confidence: 99%
“…The heptapeptide was further identified in screenings with a teratogenic serotonin receptor inverse agonist (SB-236057) [ 108 ], different rRNA targets [ 109 ] and the following protein targets: monoclonal anti-angiogenic antibody [ 110 ], melanoma inhibitory activity (MIA) protein [ 111 ], prion protein [ 112 ], chromatin high mobility group protein 1 [ 23 ] and an epitope on kidney-specific H-ATPase subunit G3 [ 113 ]. Although the binding of the LPLTPLP peptide to SB-236057, monoclonal anti-angiogenic antibody and MIA was not or could not be demonstrated [ 108 , 110 , 111 ], its affinity towards rRNA, prion protein and HMGB1 was confirmed by on-bead fluorescence assay, ELISA and Far-Western blotting, respectively [ 23 , 109 , 112 ]. Various authors have identified different proteins that contain regions with a high degree of homology to the selected LPLTPLP [ 108 , 112 , 113 ].…”
Section: Frequently Isolated Peptides/motifs Of Unknown Specificitmentioning
confidence: 99%
“…For instance, the DMS system has been used to assess embryonic delivery efficiency of compounds formulated in various vehicles (Augustine‐Rauch, Zhang et al, 2004a). In a similar application, it has also been used to determine by phenotype (in comparison to knockout morphology), relative specificity and potency of targeted gene expression inhibition by antisense oligonucleotide treatment (Augustine‐Rauch, Zhang et al, 2004b).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the standard test concentrations ranged from 0.1 to 100 µM, although there were some exceptions depending upon the study design and potency of the compound in producing general toxicity. Typical vehicles included 0.02–0.04% Tyrodes buffer (depending on the solubility of test compounds), 0.02% aged DMSO or 0.02% DMF (Augustine‐Rauch, Zhang et al, 2004a, b).…”
Section: Methodsmentioning
confidence: 99%